Fornemt skrin – i en kvindegrav fra vikingetid - Jeppesen, Jens; Schwartz, Marianne (Kuml, 2007)
A magnificent casket in a woman’s grave from the Viking Age In 2004 and 2006, Moesgård Museum excavated 21 Viking Age graves – 16 inhumation graves and five cremation graves – at Haldum Church, 20 km northwest of Århus in Eastern Jutland (fig. 1). All the graves with datable finds are from the 10th century; only one example will be presented here. The grave is a simple inhumation burial. The skeleton had completely disappeared and there were no signs of a coffin (fig. 2). About 40 cm from the western end of the grave base lay 16 glass beads scattered around over an area of about 20 x 30 cm. These comprised one red and one orange bead of opaque glass, one bead of white glass and 13 small beads of yellow glass. In the centre of the grave was a slate whetstone (fig. 3). At the eastern end was a concentration of iron fittings, and it soon became clear that these represented the remains of a casket. During excavation of the fittings a well-preserved lock turned up (fig. 4). One end of the lock’s cover plate terminates in a point with concave flared sides, while the other (broad) end divides into two prongs, between which a transverse, semicircular fitting has rusted fast. An iron band has been mounted across the pointed end; this is possibly a repair. The cover plate curves slightly along its length, which means that the lock must have been fitted on to a curved surface. The back of the lock is covered by a quadrangular plate. The distance between front and back plates is 15 mm, showing the thickness of the material within which the lock was fitted. On removing the back plate the lock construction can be seen; this is of well-known Viking Age type. It operates in such a way that the key – after having been placed into the keyhole – is pushed a little to the side so that it squeezes together the two springs of the bolt. The bolt is hereby disengaged and can be pulled back by means of a slide bar, which sits in continuation of the keyhole (fig. 5). The lock bolt is pushed into the above-mentioned, semicircular fitting. The latter comprises two plates separated by a c. 10 mm wide side piece, which gives the fitting the appearance of a small box. Three fittings of this type were found (fig. 6). Further to these components are edge and corner plates. The edge fittings all have the form of narrow, indented borders with small holes between the points. A fragment is shown lowermost on fig. 6. The corner plates have been bent back around the corner joints of the casket and are pointed at both sides. Certain other fittings were at first inexplicable. These mysterious pieces include three triangular fittings with small slide bars on their upper surface and 30 mm long bolts below (fig. 7). There are also fragments of some zip-like iron bands. These are slightly curved along their length and have a roof-shaped cross-section (fig. 8). Finally, there was a robust rivet with a square head, ingeniously worked with inwardly flared, tapered sides and crowned by a small boss. Wood imprints on the back of the fittings show that the casket was made of oak. The imprints were very useful when reconstructing the casket as they clearly show both the longitudinal direction of the wood and the depressions within it. There were imprints from a textile of coarse linen weave on the exterior of some of the edge fittings. It seems that the casket from Haldum had the same construction as the Bamberg casket (figs. 9 and 10). Each of the four sides of the Bamberg casket has, at its centre, a raised semicircular area covered by fittings. The exterior is decorated with a mask and there is a hole on the inside. The bolts of the lid presumably engaged with these holes when the casket was locked. Carved grooves in the wood under the ornamental plates of the lid lead out by way of the holes into the four semicircles. The semicircular fittings of the Haldum casket are, with regard to size and shape, completely identical to the mask fittings seen on the Bamberg casket. One of them is, as mentioned above, rusted to the lock, the bolt of which has been pushed into a hole on its inner surface. Consequently, its function is clear; it is also clear that the casket was locked when placed in the grave. The lid of the Bamberg casket is divided by ornamental bands into four triangular fields (fig. 11). In one of these fields (A), a T-shaped keyhole is apparent, and in continuation of this there is a slot for a slide bar. In the field opposite (C), there is a small hole and each of other fields (B and D) has a partly damaged slide-bar slot. We are so fortunate that the fittings surviving from the Haldum casket include slide bars, bolts and other lock parts that have been lost from the Bamberg casket. It is possible to place the lock and the various fittings from the Haldum casket in a square of the same dimensions as the lid of the Bamberg casket. In the fields created by arranging the zip-shaped fittings to form a diagonal cross, there is space for the lock and the three triangular fittings (fig. 11). The excavation photo in fig. 12 shows the three types of fittings in their original positions. In continuation of the keyhole, the lock has a small slide bar whereby the bolt was pushed into one of the semicircular fittings (side A). The forks of the lock plate extend down on either side of this fitting, demonstrating that there was a central depression in the four sides of lid in order to accommodate the semicircular fittings, as seen on the Bamberg casket. In the triangular fitting, which was located opposite the lock (side C), there is also a small slide bar but no slot in which it could move. Similarly, the wood imprint on the back shows that there was no depression to allow a bolt to be pushed back and forth. On the corresponding side of the lid of the Bamberg casket, the carved depression for the bolt is less marked than on the other sides. On the two remaining triangular fittings from the Haldum casket, the slide bars are located in 15 mm long slots (sides B and D). On the reverse, clear depressions are seen in the wood imprint in which the bolts were slid back and forth (fig. 13). If the fittings are arranged in this way, all the pieces show the same longitudinal direction of the wood imprints on their reverse. This indicates that the casket lid was made from one piece of wood. As is apparent from the carvings on the Bamberg casket, the slide bars of the closing mechanism were located close to the centre of the lid. The hidden grooves for the bolts run from here, under the ornamental plates, and emerge at the edge of the lid. Apparently, the Haldum casket did not have ornamental plates screening the grooves for the bolts. As a consequence, the triangular fittings with the slide bars were placed close to the edge of the lid so that they met the semicircular fittings. In this way it was only necessary to have short grooves for the bolts, and these were covered by the fittings. The way in which the lid and the casket are fitted to one another, together with the absence of hinges, indicates that the lid was loose and was lifted completely off in order to open the box. The bolt opposite the lock (side C) was permanently pushed forwards and was the first to be pushed into the matching semicircular fitting, after which the lid was tilted down into place. After this, the two bolts at the sides (B and D) were extended to keep the lid fastened. Finally, the lock’s bolt was pushed into place and the casket was then locked. By observing the curvature of the striker plate, the triangular fittings, the zip-shaped fittings and some of the edge fittings, which have a curved cross-section, it is possible to reconstruct the shape of the lid (see fig. 10). Its height was c. 45 mm. The rivet must have marked the centre of the lid, corresponding to the cruciform fitting on the lid of the Bamberg casket. The body of the Bamberg casket was assembled by pushing the end surface of one side against the side surface of the next. The wood imprints on the corner plates of the Haldum casket show that the same technique was also used here. It is apparent from these wood imprints, as well as the distance between front and back of the semicircular fittings, that the sides were about 10 mm thick. The wood imprints on the inner side of the semicircular fittings show that the tree rings on the side pieces ran vertically. Had they run horizontally, this would have rendered these curves a weak point. The surviving remains of the Haldum casket show a surprising similarity to the Bamberg casket. There is, however, nothing to indicate that the casket from Haldum was as magnificently decorated, but the now completely vanished oak wood casket may possibly have been decorated with both carvings and paintings. Furthermore, the casket originally had edge fittings greater than 3 mm in width which, in themselves, would also have constituted considerable ornamentation. This fact became evident from construction of the replica (fig. 14). The latter also confirmed the reconstruction of the Haldum casket and its complicated closing mechanism. The Haldum find shows that the Bamberg casket, with its special construction, is not unique, and two further finds kept at Danmark’s National Museum indicate that caskets of this type were perhaps more widespread than previously assumed. One is a cruciform fitting of gilt bronze (fig. 15). The four transepts end in stylised animal heads, and at the centre is a hemispherical raised area. At the centre of the lid of the Bamberg casket there is a cruciform fitting also with animal heads at the ends of the transepts, and in the middle sits a hemispherical rock crystal (fig. 16). The similarity to the former fitting is striking, and it seems likely that the artefact represents a lid fitting for a casket of Bamberg type. The other artefact is a cruciform fitting of sheet bronze with open-work sections between the limbs of the cross and a circular hole at its centre (fig. 17). The fitting is part-finished and of the same type as the first mentioned, but a somewhat different variant. The two fittings were found in an old ford across Halleby Å in Western Zealand near the rich Viking Age settlement at Tissø. They were recovered together with the remains of a tool chest. The grave in which the Haldum casket was found is presumed to be that of a woman because beads and small locked caskets are typical woman’s equipment in Viking Age graves. However, such grave goods have also been found in a few cases in men’s graves. The whetstone gives no indication of the sex of the deceased because this type of artefact was commonly included as grave goods in both men’s and women’s graves. The great similarity of Haldum casket to the Bamberg casket dates the grave to the second half of the 10th century. The style of the Bamberg casket indicates that it was produced in Denmark or Southern Scandinavia. Recently, however, attention has been drawn to the fact that the Mammen style also appears over a wider area. Finds from areas where the Vikings settled outside Scandinavia– from The British Isles to Russia – indicate that craft work in the Mammen style could also have been produced there. The finding of the Haldum casket does, however, add weight to the conclusion that the Bamberg casket was produced in Denmark. This is also the case for the two fittings from Halleby Å if the interpretation presented here is correct. However, whether boxes of this type were produced in one particular place or are the work of one or more travelling craftsmen remains to be ascertained. Jens Jeppesen Marianne Schwartz Moesgård Museum